Analysis of the Need for Pop Up Book Learning Media in Science and Science Lessons for Class V Students of SDN 2 Tanggung Blitar City - Yuniawatika, Yuniawatika; Fiqriyah, Nadhirotul; Ichsandari, Anisa; Putri R.S, Angela; Susilowati, Agis (Universitas Negeri Malang, 2024)
This reseach aims to analyze needs of learning media in class V and as an innovation in learning media for cultural heritage material so that it can attract students' interest in learning. The problems found are students have difficulty understanding cultural heritage material because it presents a lot of reading material, in learning process teachers only use thematic books without additional books, and teachers have not linked realistic examples related to cultural heritage in learning. The study use qualitative by collecting data from interviews, questionnaires and observation techniques. The results of analysis conducted 81% of students need learning media. These results indicate that fifth grade students really need learning media as learning support. Based on this, learning media must integrate technology that can attract the attention of students by being equipped with text, 2D and 3D images, and interactive evaluations and encourage student interest in understanding cultural heritage IPAS material.